Evaluation of the delta neutrophil index from an automated blood cell analyser in septic dogs. (December 2017) - Troìa, R.; Agnoli, C.; Calipa, S.; Segalina, S.; Murgia, E.; Gruarin, M.; Dondi, F.; Giunti, M.
Highlights: The delta neutrophil index (DNI) is a potential marker for canine sepsis. The DNI appears to have value in predicting septic shock in dogs. The DNI is correlated with the presence of immature and toxic neutrophils evaluated on blood smears in dogs with sepsis. Abstract: Immature granulocytes (IG) are a marker of severe inflammatory states in human beings and animals, and have been linked to a diagnosis of sepsis and poor prognosis. The delta neutrophil index (DNI), automatically calculated by a haematological analyser, provides an estimate of circulating IG. In particular, an increased DNI value has been associated with the severity of sepsis, and mortality, in critically ill human beings. The aims of this study were to determine the DNI reference interval (RI) in healthy dogs, and to evaluate its diagnostic and prognostic significance in dogs with sepsis. A total of 118 dogs with sepsis undergoing a complete blood cell count (CBC) at the time of hospital admission were included retrospectively. Dogs with sepsis were compared to 20 dogs with primary immune-mediated haemolytic anaemia (IMHA) and 99 healthy controls. The DNI RI was set from 0 to 9.2%. The DNI was significantly higher in dogs with sepsis compared to dogs with IMHA and healthy dogs ( P < 0.001), and significantly higher in dogs with septic shock compared to septic dogs without circulatory failure ( P < 0.03). No differences were detected between survivors (78/118) and non-survivors (40/118). Septic dogs with a DNI above the RI had significantly higher frequencies of IG and toxic neutrophil changes on manual blood smear evaluation ( P = 0.03 and P < 0.001, respectively). The DNI had a fair performance in identifying dogs with sepsis in this population and predicted septic shock. Larger prospective studies are needed to validate DNI measurement in dogs and to test its clinical utility.